2021
DOI: 10.3390/en14092620
|View full text |Cite
|
Sign up to set email alerts
|

Energy Harvesting and Water Saving in Arid Regions via Solar PV Accommodation in Irrigation Canals

Abstract: The Egyptian irrigation system depends mainly on canals that take water from the River Nile; nevertheless, the arid climate that dominates most of the country influences the high rate of water losses, mainly through evaporation. Thus, the main objective of this study is to develop a practical approach that helps to accommodate solar photovoltaic (PV) panels over irrigation canals to reduce the water evaporation rate. Meanwhile, a solar PV panel can contribute effectively and economically to an on-grid system b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…So, the Nile Delta region is a warm zone and is generally dry, with an annual rainfall of less than 40 mm. The moisture ranges from 45 to 84%, while water evaporation rate is between 2.5 and 15 mm (El-Arabi et al, 2013;Alhejji et al, 2021).…”
Section: Study Areamentioning
confidence: 99%
“…So, the Nile Delta region is a warm zone and is generally dry, with an annual rainfall of less than 40 mm. The moisture ranges from 45 to 84%, while water evaporation rate is between 2.5 and 15 mm (El-Arabi et al, 2013;Alhejji et al, 2021).…”
Section: Study Areamentioning
confidence: 99%
“…7 The solar panel and diesel generator reduced the considerable amount of LCOE. 8 The solar water pumping system and the existing system run by conventional energy sources have been economically tested in the Faculty of Engineering and Technology (FET) in Jamia Milia and concluded that the total cost of the solar photovoltaic (SPV) system is around 10 lac that will return in 4 years payback period. However, the total life of the pump was 20 years then it will supply the water for up to 16 years without spending any cost.…”
Section: Introductionmentioning
confidence: 99%
“…The economic feasibility of the PV and diesel‐operated pump have been checked and model comparison was done based on power capacity at different locations and different conditions of the environment 7 . The solar panel and diesel generator reduced the considerable amount of LCOE 8 . The solar water pumping system and the existing system run by conventional energy sources have been economically tested in the Faculty of Engineering and Technology (FET) in Jamia Milia and concluded that the total cost of the solar photovoltaic (SPV) system is around 10 lac that will return in 4 years payback period.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, much research has been carried out on the water-energy nexus in irrigation systems [4][5][6][7][8]. The nexus between water and energy in the CPSIDs is getting closer.…”
Section: Introductionmentioning
confidence: 99%